Implementation of GCG Principles in Distribution of Credit in SOE/BUMD Bank - Indra Gunawan Purba (Polit Journal Scientific Journal of Politics, 2021)
The aims this study is to find out Implementation of GCG Principles in Distribution of Credit in SOE/BUMD Bank. This study use normative juridical research. The resul in this study shows that The board of directors and management of BUMN/BUMD banks absolutely must understand and apply the principles of GCG, especially in lending by applying the principles of GCG to prevent the occurrence of credit that has the potential to harm the company due to the lack of prudence and responsibility of officers to carry out loans. verification of customer data in the field. State-owned/BUMD Banks are required to be guided by the principles of GCG in implementing management so that the achievement of the goals and objectives, especially through the distribution of banking credit to the public and debtor customers can be obtained properly and maximally or at least not experiencing bad loans which have the potential to cause economic losses for the Bank BUMN/BUMD.